The ‘myth of Hydroxychloroquine (HCQ) as post-exposure prophylaxis (PEP) for the prevention of COVID-19’ is far from reality - Deba Prasad Dhibar; Navneet Arora; Deepak Chaudhary; Ajay Prakash; Bikash Medhi; Neeraj Singla; Ritin Mohindra; Vikas Suri; Ashish Bhalla; Navneet Sharma; Mini P. Singh; P. V. M. Lakshmi; et al. (Scientific Reports, 2023)
Abstract The efficacy of Hydroxychloroquine (HCQ) as post-exposure prophylaxis (PEP) for the prevention of COVID-19 was contentious. In this randomized control double-blind clinical trial, asymptomatic individuals with direct contact with laboratory-confirmed COVID-19 cases were randomized into PEP/HCQ (N = 574) and control/placebo (N = 594) group. The PEP/HCQ group received tablet HCQ 400 mg q 12 hourly on day one followed by 400 mg once weekly for 3 weeks, and the control/Placebo group received matching Placebo. The incidence of COVID-19 was similar (p = 0.761) in PEP [N = 24 out of 574, (4.2%)] and control [N = 27 out of 594, (4.5%)] groups. Total absolute risk reduction for the incidence of new-onset COVID-19 was -0.3% points with an overall relative risk of 0.91 (95% confidence interval, 0.52 to 1.60) and the number needed to treat (NNT) was 333 to prevent the incident of one case of COVID-19. The study found that, PEP with HCQ was not advantageous for the prevention of COVID-19 in asymptomatic individuals with high risk for SARS-CoV-2 infection. Though HCQ is a safer drug, the practice of irrational and indiscriminate use of HCQ for COVID-19 should be restrained with better pharmacovigilance.